Sexual dysfunction and its determinants among women infected with HIV. Issue 3 (22nd March 2017) - Agaba, Patricia A.; Meloni, Seema T.; Sule, Halima M.; Agaba, Emmanuel I.; Idoko, John A.; Kanki, Phyllis J.
Abstract: Objective: To describe the prevalence of female sexual dysfunction (FSD) and its determinants among women with HIV infection enrolled for care and treatment in an ambulatory care setting. Methods: A questionnaire‐based cross‐sectional survey was conducted among women attending the HIV clinic of Jos University Teaching Hospital, Nigeria, between March 2013 and February 2014. The self‐administered Female Sexual Function Index (FSFI) was used to assess FSD; a score of less than 26.55 indicated FSD. Pearson coefficient was used to assess interdomain correlation, and multiple linear regression was used to identify factors associated with FSD. Results: Among 370 participants, 330 (89.2%, 95% confidence interval [CI] 85.6%–92.2%) had FSD. The overall median FSFI score was 19.2 (interquartile range [IQR] 6.4–23.9). The arousal domain had the lowest subscore (median 2.7, IQR 0.0–3.6). The highest interdomain correlations were between lubrication and orgasm ( r =0.87), arousal and lubrication ( r =0.84), and arousal and orgasm ( r =0.81) domains. Satisfactory health (β=3.34, 95% CI 1.16–5.52) and history of alcohol use (β=2.38, 95% CI 0.28–4.47) were independently associated with FSD. Conclusion: FSD was prevalent among women with HIV infection. Care providers need to routinely address FSD as part of a comprehensive care package in the study setting. Abstract : Sexual dysfunction was found to be highly prevalent among women infected with HIV in Nigeria.